Family resilience and social support as mediators of caregiver burden and capacity in stroke caregivers: a cross-sectional study - Xu, Qihang; Ma, Jingjing; Zhang, Yiqing; Gan, Jiehua (Frontiers in Psychology, 2024)
Introduction Caring for stroke survivors poses significant challenges to survivors and caregivers; understanding these relationships can inform targeted interventions and support systems. Aim This study investigates the influencing factors of caregiver burden and the potential mediating roles of family resilience and perceived social support between caregiver burden and caregiver capacity. Design This is a cross-sectional study. Methods The participants in this study included 462 stroke survivors and their primary caregivers from Ningbo Lihuili Hospital in Zhejiang Province, China. Primary caregivers completed several assessments, including the Shortened Chinese Version of the Family Resilience Assessment Scale (FRAS), the Perceived Social Support Scale (PSSS), the Zarit Caregiver Burden Interview (ZCBI), and the Family Caregiver Task Inventory (FCTI). The ZCBI was used to evaluate caregiver burden, while the activities of daily living (ADL) were assessed for stroke survivors to measure their actual level of dependence. The mediating effect of family resilience was estimated using the bootstrap method through Jamovi version 2.3.0 with the mediation plug-in, while controlling for sociodemographic variables. Results The results showed that caregiver burden was influenced by stroke survivors’ level of dependence on activities of daily living (ADL), caregiver education level, caregiver health status, and average daily care time. The family resilience mediated the relationship between caregiver burden and caregiver capacity (b = 0.141; 95% confidence interval: 0.091 to 0.176). Additionally, perceived social support mediated the relationship between caregiver burden and caregiver capacity (b = 0.080; 95% confidence interval: 0.041 to 0.110). Conclusion These findings indicate that enhancing family resilience and perceived social support can be strategies for alleviating caregiver burden. Clinical practitioners should actively assess the family resilience and social support of stroke survivors, and implement interventions that promote resilience and strengthen social support, thereby reducing caregiver burden and improving the health outcomes of stroke survivors.